The Fuzzy Concept of Idiom and What It Might Mean for Bilingual Dictionaries - Andrejs Veisbergs (Baltic Journal of English Language, Literature and Culture)
Linguistic categories were developed as tools for describing language systems and making them easier to learn. However, like many theoretical concepts and systems, they do not fully represent the real world and, in some cases, seek to imprison linguistic units within a well-ordered system – a procrustean bed as it were. Besides, although the most general categories are universal, the lower-ranking ones are often language-specific. Idiom (or phraseologism) is a very unclear linguistic concept, subject to never-ending debate. However, a strict adherence to categorisation is observable in practical bilingual lexicography and phraseography. This may lead to unwanted compartmentalisation and a skewed product. The conventional practice in bilingual lexicography is to provide B-language idiom equivalents or analogues for A-language idioms and B-language lexical items for A-language words. B-language idioms are not normally provided for A-language words and vice versa. This reflects thinking in terms of structures, rather than of semantic equivalence. The sharp demarcation of structures in dictionaries erects needless barriers by imposing the theoretical concepts of idiom, compound, derivative and metaphorical lexical item on to practical lexicography. The phrase-compound-derivative-idiom divide is often quite arbitrary and changes over time. Moreover, the only functional equivalent for a word is often an idiom and vice versa.